An Advanced 'clickECM' That Can be Modified by the Inverse‐Electron‐Demand Diels‐Alder Reaction. (17th August 2021) - Nellinger, Svenja; Rapp, Mareike A.; Southan, Alexander; Wittmann, Valentin; Kluger, Petra J.
Abstract: The extracellular matrix (ECM) represents the natural environment of cells in tissue and therefore is a promising biomaterial in a variety of applications. Depending on the purpose, it is necessary to equip the ECM with specific addressable functional groups for further modification with bioactive molecules, for controllable cross‐linking and/or covalent binding to surfaces. Metabolic glycoengineering (MGE) enables the specific modification of the ECM with such functional groups without affecting the native structure of the ECM. In a previous approach (S. M. Ruff, S. Keller, D. E. Wieland, V. Wittmann, G. E. M. Tovar, M. Bach, P. J. Kluger, Acta Biomater . 2017, 52, 159–170), we demonstrated the modification of an ECM with azido groups, which can be addressed by bioorthogonal copper‐catalyzed azide‐alkyne cycloaddition (CuAAC). Here, we demonstrate the modification of an ECM with dienophiles (terminal alkenes, cyclopropene), which can be addressed by an inverse‐electron‐demand Diels‐Alder (IEDDA) reaction. This reaction is cell friendly as there are no cytotoxic catalysts needed. We show the equipment of the ECM with a bioactive molecule (enzyme) and prove that the functional groups do not influence cellular behavior. Thus, this new material has great potential for use as a biomaterial, which can be individually modified in a wide range of applications. Abstract : Metabolic glycoengineering was employed to incorporate dienophiles (terminal alkenes and a cyclopropene) into the extracellular matrix (ECM) of adipose‐derived stem cells (ASCs). A subsequent inverse‐electron‐demand Diels‐Alder (IEDDA) reaction allowed the equipment of the ECM with bioactive molecules, opening numerous applications.